Mariposa blues - Koertge, Ronald (New York: Avon Books, 1993)
Returning to California for the summer to help train and race thoroughbreds, thirteen-year-old Graham tries to cope with the changes in his relationships with his dad and best friend Leslie and become an individual in his own right.
Originally published: Boston : Little, Brown, c1991.
8 13 18
Keywords: Horse racing -- Fiction; Fathers and sons -- Fiction; Friendship -- Fiction